Study Geo service Of the old urban structure In the city of Damascus - Kamash, Faesal; Ahmad, Dareen (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Extremism in the modernization construction of the world in general and in the Arab world especially, and move away appearances Imran cities gradually from their original forms and indifference to the nature of the medium in which you are in it, move architectural heritage and ancient cities issue in recent years, we have acquired a great importance to maintain. Here are already Vanguards explicit positions recite them interested in inhabitedness city, ranging from the foundations of the province of the movement of radical sometimes obscured her face to talk for fear of privacy ideological nationalism of innovators stream would call for a return to the old attracted of the fear of the loss of part of the Arab-Islamic architecture of civilization, and the movement of dissolute to the old movement from the West haphazardly and it describes the ultra-conservative and reactionary intransigence. And between these and the reaction of moderate considering the successful experiences of the past we are dealing with creative mind, in search of the spirit of heritage to create them the achievements of urban living, her last Features civilized authentic spirit of heritage, based on local ground suitable in the image and The content of the environment Levantine. The issue of architectural heritage theme in inhabitedness newly signed Well, it deals with the architectural achievements of the past in order to spare it harm in continuing damage to threaten its existence.